Sport and character reclaiming the principles of sportsmanship - Clifford, Craig Edward 1951-; Feezell, Randolph M. 1950- (Champaign, IL Human Kinetics, 2010)
In an era when our nightly news is filled with reports of athletes run amok on the field, on the court, and on the street, and when cheating by players and coaches has become a part of the daily discourse, sportsmanship has never been a more timely topic. According to a national survey of high school athletes conducted by the Josephson Institute, 40% of boys surveyed and 25% of girls surveyed see nothing wrong with using a stolen playbook sent by an anonymous supporter before a big game; 54% of male football players, 49% of male basketball players, and 18% of females in all sports approve of trash talking; and 34% of boys surveyed and 12% of girls surveyed approve of a coach trying to pump up the team by swearing at officials to get ejected from the game. These statistics illustrate the importance of clarifying the boundaries of healthy competition and modeling the principles of fair play. Sport and Character: Reclaiming the Principles of Sportsmanship can help those involved in sport tackle the important lessons of sportsmanship by encouraging them to practice and teach respect for opponents, coaches, officials, teammates, and the game. Using examples from common situations that occur on and off the field, Sport and Character brings to life what is required in order to be a good sport. Special "News Breaks" incorporated throughout the text present practical examples of sportsmanship drawn from current sport news, including articles about Michael Phelps, Shawn Johnson, Jimmy Rollins, and Nastia Liukin. Inspirational quotes by Phil Jackson, John Wooden, and Mickey Mantle add vitality to this tool for building good athletes and in turn good citizens. Sport and Character: Reclaiming the Principles of Sportsmanship is endorsed by the American Sport Education Program (ASEP). Established by world-renowned sport psychologist Rainer Martens, ASEP has trained more than 1.5 million coaches since its inception in 1981.
Part I. Thinking About Sportsmanship -- Chapter 1. Reflecting on Your Own Experience -- Chapter 2. Sportsmanship and the Nature of Sport -- Part II. The Principles of Sportsmanship -- Chapter 3. Respect for Opponents -- Chapter 4. Respect for Teammates and Team -- Chapter 5. Respect for Officials -- Chapter 6. Respect for the Game -- Chapter 7. Respect Between Players and Coach -- Part III. Thinking About Sport and Life -- Chapter 8. Sport, Society, and Education -- Chapter 9. Beyond Sport.
Includes bibliographical references
Also available in print version
Keywords: Sportsmanship